Discovery of a new species of Paronesimoides (Crustacea: Amphipoda: Tryphosidae) from a cold seep of Mariana Trench. Issue 5 (16th February 2022) - Tomikawa, Ko; Watanabe, Hiromi Kayama; Tanaka, Katsuhiko; Ohara, Yasuhiko
ABSTRACT: We describe a new tryphosid amphipod, Paronesimoides calceolus sp. nov., from the Shinkai Seep Field, Mariana Trench, at a depth of 5689–5683 m. This is the first species of Paronesimoides to be described in the Mariana Trench and the deepest record of the genus. Paronesimoides calceolus sp. nov. differs from its congeners in characteristics of its head, antennae, mandible, coxae, gnathopods and telson. A key to the Paronesimoides species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:87787DD8-FEEB-43C1-AEAA-40C37B021768